Chemical composition of the leaves of tea bush (Ocimum gratissium L.) (Bangladesh Journal of Scientific and Industrial Research, 2015)
Tea bush leaves are important in the preparation of soups. Crude fat was 5.20g/100g. High value results (g/100g): protein (28.9), carbohydrate (36.2), ash (9.40), fibre (14.1); fatty acid (4.16g/100g) with energy value (154kJ/100g). High major minerals were: Ca, Mg, K and P, high trace minerals were: Fe, Cu, Mn and Zn. Mineral ratios within nutritional standards: Na/K, Ca/P and [K/(Ca + Mg)]. In amino acid composition, highest concentrated amino acid was Glu (11.0g/100g), second was Leu (7.65g/100g), total amino acid (87.2g/100g). Essential amino acid (with His) was 42.5g/100g (48.7%). Quality parameters obtained in the results: Leu/Ile (1.59), % Cys/TSAA (42.3), P-PER (2.49) and EAAI (1.18). On quality criteria, Lys was limiting in the three criteria used. Fatty acid had values of SFA (30.9%), MUFA (5.60%), PUFA (63.5%), PUFA/SFA (2.06), n-6/n-3 (1.52), EPA/DHA (1.39). Total phospholipids (44.1mg/100g) with phosphatidylcholine (15.9), phosphatidylinostitol (14.9) predominating. Cholesterol was 0.00mg/100g, sitosterol was 26.3mg/100g (61.5%).Bangladesh J. Sci. Ind. Res. 50(2), 93-108, 2015